Building on Evidence : A Situational Analysis of the HIV Epidemic and Policy Response in Honduras - World Bank (Washington, DC, 2017)
This paper summarizes key findings of the epidemiological, response and policy synthesis analysis carried out in Honduras in 2007, as part of the preparation of the new national HIV/AIDS strategy, PENSIDA III, (National Strategic Plan to Fight HIV/AIDS - Plan Estrategico Nacional de Lucha Contra el VIH/SIDA) 2008-2012. It presents the most recent data on HIV prevalence, and the results of models that estimate sources of infection and likely patterns and trends in future prevalence. The paper also describes how these data and projections have been incorporated into the design of Honduras' response to the epidemic, grounding PENSIDA III's strategic direction in the data on the epidemic and response in Honduras, building and improving on previous experience.